2014
DOI: 10.3389/fnhum.2014.00426
|View full text |Cite
|
Sign up to set email alerts
|

Altering second-order configurations reduces the adaptation effects on early face-sensitive event-related potential components

Abstract: The spatial distances among the features of a face are commonly referred to as second-order relations, and the coding of these properties is often regarded as a cornerstone in face recognition. Previous studies have provided mixed results regarding whether the N170, a face-sensitive component of the event-related potential, is sensitive to second-order relations. Here we investigated this issue in a gender discrimination paradigm following long-term (5 s) adaptation to normal or vertically stretched male and f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 58 publications
2
7
0
Order By: Relevance
“…Note also that both the N170 and P200 shape caricature effects in the Kaufmann and Schweinberger (2012) study were monotonically related to the level of caricaturing (35% vs. 70%), and the N170 effects were not consistent for moderate levels of caricaturing. It is therefore plausible that the reliability of an early onset of shape effects in the N170 time-window depends on both type and degree of shape manipulation, and this idea appears to be consistent with the available evidence (Caharel et al, 2009;Schulz et al, 2012a;Vakli et al, 2014).…”
Section: Discussionsupporting
confidence: 76%
“…Note also that both the N170 and P200 shape caricature effects in the Kaufmann and Schweinberger (2012) study were monotonically related to the level of caricaturing (35% vs. 70%), and the N170 effects were not consistent for moderate levels of caricaturing. It is therefore plausible that the reliability of an early onset of shape effects in the N170 time-window depends on both type and degree of shape manipulation, and this idea appears to be consistent with the available evidence (Caharel et al, 2009;Schulz et al, 2012a;Vakli et al, 2014).…”
Section: Discussionsupporting
confidence: 76%
“…Results of visual ERP studies of adaptation have been variable. Several studies reported attenuation of some ERP components (Schweinberger et al, 2004 ; Fiebach et al, 2005 ; Kovács et al, 2006 ; Harris and Nakayama, 2007 ; Huber et al, 2008 ; Caharel et al, 2009 ; Vizioli et al, 2010 ; Vakli et al, 2014 ). However, some of the above and other studies (Puce et al, 1999 ; Andrade et al, 2015 ) also observed repetition enhancement, or no change.…”
mentioning
confidence: 99%
“…For familiar faces over the right hemisphere (RH), there was a main effect of caricature level, F (3,90) = 2.75, p = .047, η p 2 = .084, due to a linear trend, F (1,30) = 8.98, p = .005, η p 2 = .230, and no effects of face type. Over the LH for unfamiliar faces there was a main effect of caricature level, F (3,90) = 8.78, p < .000, η p 2 = .226, ε HF = .856, which interacted with face type, F (6,180) = 3.25, p = .005, η p 2 = .098: Main effects of caricature level were found for unfamiliar SC, F (3,90) = 12.74, p < .001, η p 2 = .298, and FC, F (3,90) = 3.35, p = .022, η p 2 = .100, due to linear trends ( F [ 1 , 30 ] = 38.48, p < .001 η p 2 = .562 for SC, and F [ 1 , 30 ] = 12.56, p = .001, η p 2 = .295 for FC; Fig 4 ). Finally, over the RH for unfamiliar faces there was a main effect of caricature level, F (3,90) = 3.43, p = .020, η p 2 = .103, due to a linear trend, F (1,30) = 10.48, p = .003, η p 2 = .259, with no effects of face type.…”
Section: Resultsmentioning
confidence: 98%
“…The N170 component shows a high degree of sensitivity to faces compared to other stimulus classes [ 25 ], is typically not affected by familiarity [ 26 28 ], and is often associated with face detection and structural encoding [ 21 , 22 ]. Note also that N170 is affected by facial shape [ 29 , 30 ] and has been shown to be larger for shape caricatures [ 31 , 32 ]. The subsequent P200 has been found to be smaller for shape caricatures [ 24 , 31 ] and larger for anti-caricatures [ 24 ], and may thus be a marker of perceived shape typicality.…”
Section: Introductionmentioning
confidence: 99%